Global surgical collaboration to treat bladder exstrophy-epispadias in India led to a larger geographical catchment area - Katelyn Spencer; Rakesh Joshi; Jaishri Ramji; Sahar Eftekharzadeh; Pramod Reddy; Douglas Canning; Joao Pippi-Salle; Paul Merguerian; Anjana Kundu; Jennifer Frazier; Dana Weiss; Aseem Shukla (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background A gap of care exists in low- and middle-income countries (LMICs) for patients with complex urogenital abnormalities, such as bladder exstrophy-epispadias complex (BEEC). A successful primary surgical repair is critical for optimal long-term outcomes for BEEC, but the availability of such a complex procedure is limited by the expertise needed to deliver a successful initial repair. We hypothesize that a long-term, multi-institutional collaboration based at a tertiary institution in a LMIC may improve outcomes for BEEC by encouraging earlier referrals for the first repair, rather than after failed repairs, and also increase the geographical catchment area by encouraging more distant referrals, once the availability of care becomes widely known. # Methods A long-term collaboration between two US academic research centers and the Civil Hospital in Ahmedabad, Gujarat, India was formed in 2009. This collaboration expanded later to include another US and one Middle Eastern hospital system. The entire post-operative cohort of the collaboration was recalled in 2019 and 2020, when epidemiology and demographic surveys were obtained from 82 patients. # Results Since 2009, the collaboration has grown overall. The geographical catchment area for referrals and distance traveled by patients to reach the collaboration site has increased to include nine states in India and surrounding countries in Southeast Asia (P = 0.044). Patients traveling from farther distances tended to be of higher socioeconomic status than local referrals (P = 0.041). # Conclusions The success of the International Bladder Exstrophy Consortium to improve the care for BEEC patients in India and Southeast Asia is visible from its changing demographics. Patients, some even from families of a higher socioeconomic status, are traveling farther to receive care at a government-funded tertiary hospital. While not all positive benefits of a global surgery collaboration regarding earlier and primary referrals have been achieved, the collaboration is seeing benefits that align with a staged process of referrals. The continued commitment to creating a center of excellence is a model for sustained success for global surgery collaborations.